Protecting elderly people in Bangladesh: an overview - Ferdousi, Nahid (Penerbit Universiti Kebangsaan Malaysia, 2019)
The elderly rights have tended to become an issue throughout the world. Old age is the closing period of life span. During this period of age, most people cannot do anything by their own efforts. They need materialistic and nonmaterialistic support from others. For this, reason age is considered as a social problem. Equally, they are neglected and abused from family and society. Protecting the rights of elderly people is a newly introduced phenomenon in Bangladesh. The developed countries have paid more attention on social support system and welfare based legal framework. In Bangladesh, the elderly problem is usually ignored as there is no comprehensive legal framework with relation to respecting, promoting and protecting the rights of older people. The first law has been enacted in 2013 (the Maintenance of Parents Act) to ensure the parents’ maintenance by their children. Nevertheless, there is no separate welfare policy existing for the elderly in the country yet. It is a challenge to deliver the essential health care service, social security facilities through national laws. The purpose of the study is to overview the existing legal framework of elderly rights and to discuss the major challenges of older people under the existing social security programme in Bangladesh.